Stichorchis subtriquetrus (Digenea: Paramphistomatidae) from Eurasian beaver (Castor fiber) in the Czech Republic - Máca, Ondřej; Pavlásek, Ivan; Vorel, Aleš (Parasitology research, 2015)
Between March 2012 and April 2014, we performed post-mortem parasitological examinations of 11 Eurasian beavers (Castor fiber Linnaeus, 1758) from the basins of four main rivers (Dyje, Labe, Morava, Vltava) in the Czech Republic. The cause of death of five adult animals was unknown, three adult animals died after being hit by cars, while one young and one adult as a result of serious injuries and one juvenile male drowned. The trematode Stichorchis subtriquetrus (Rudolphi, 1814) Lühe, 1909 was only found in the caecum body and caecum apex of nine beavers (82%), with no significant differences in parasite intensity among beavers. The highest number of trematodes (271) occurred in an adult female in July 2013; while a range of 1-57 individuals were found in other positive beavers. S. subtriquetrus size in both parts of the caecum was 11.0-17.0 × 5.5-8.0 mm (mean 14.3 × 6.9 mm). Results demonstrated that for the optimal detection of eggs, it was necessary to examine at least 10 g of faeces with a new modified method of sedimentation. The size range of 30 eggs was 157.1-182.5 × 99.3-109.8 μm (mean 168.0 × 104.4 μm). There were no differences in prevalence and seasonal occurrence of S. subtriquetrus between male and female beavers. We did not find any other intestinal endoparasites or tissue parasites (Sarcocystis spp., Trichinella spp.).
Keywords: Animals; Česká republika; Trematoda; hlodavci; Female; mužské pohlaví; zvířata; infekce červy třídy Trematoda; Male; Trematode Infections; Czech Republic; ženské pohlaví; Rodentia